THE ROLE OF COMPUTER-BASED TEST CONTROL IN THE OBJECTIVENESS OF ASSESSING STUDENTS’ KNOWLEDGE LEVEL - Bodiaka, Volodymyr (SWorld-Ger Conference proceedings, 2025)
One of the methods of improving the quality of education is the introduction of computer-based test control. As is known, along with its advantages, computer-based test control has a number of disadvantages, which do not allow for a full assessment of the